Heart rate and blood lactate concentration during on-snow training in college cross country skiers - Gibbons, T. P.; Watts, P. B. (Medicine & Science in Sports & Exercise, 1993)
Heart rate (HR) and blood lactate concentrations (BLC) are used to monitor training intensities in cross country skiers. It is assumed that HR-BLC relationships derived in the laboratory will hold for various training intensities in the field. Expert skiers (M = 5, F = 3) were laboratory tested to determine training intensities I, II, III, and IV. Using freestyle techniques, overdistance training (Levels I and II) and interval training (Levels III and IV) were performed with HR and BLC being monitored frequently throughout the training sessions. 1. HR was similar for both Levels I and II training, and did not vary significantly during any of the four training experiences (it was consistent during each session). 2. Level IV training reflected both HR and BLC that were measured in a race. 3. There was little difference between HR for Levels III and IV (173 vs 179) but large differences in BLC (3.86 vs 11.14 m/mol). This suggested little relationship between HR and BLC in interval work at training. 4. During interval training, although HR may remain stable during the session, BLC can vary considerably. Implication: There is little relationship between HR and BLC during interval training.